Keadilan Ekologis dan Konstruksi Sosial tentang Alam: Tinjauan Filosofis-Kritis atas Konflik Pemanfaatan Lahan di Indonesia - Triyaka Lisdiyanta; Zulkarnain Awat Amir; Rahmad Salam; Andriansyah Andriansyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Land use conflicts are complex phenomena that are not only related to legal and policy issues but also rooted in how humans understand and interpret nature. This study examines land use conflicts through the perspectives of ecological justice and the social construction of nature using a philosophical-critical approach. Drawing on qualitative literature review and critical discourse analysis of environmental philosophy, justice theory, and land-use policy discourse, the study develops a conceptual framework for analyzing how competing constructions of nature shape conflict trajectories. The analysis demonstrates that anthropocentric discourses tend to legitimize exploitative land-use practices and marginalize the intrinsic value and ecological functions of nature. It also identifies a structural clash between state–corporate constructions of land as an economic asset and local/community constructions of land as a socio-cultural and ecological lifeworld, reinforced by power relations and policy regimes that remain insensitive to ecological justice. The study concludes that land-use conflicts reflect systemic ecological injustice and therefore require a philosophical reconstruction of the human-nature relationship, positioning ecological justice as a normative foundation for land governance and sustainable policy formulation.